An improved method to visualize two regions of interest synchronously in microfluidics. (April 2020) - Zhang, Jingzhi; Lei, Li; Liang, Fushun; Li, Huiling; Sundén, Bengt; Wu, Zan
Abstract: Multiphase flow in mini/micro channels has been widely studied for its potential in many industrial applications. The normal experimental method cannot capture two separate regions of interest (ROI) with a long distance synchronously for the limited field of views. In order to solve this problem, an improved experimental method is proposed and validated with experimental results. Prism groups are applied to reflect the two regions of interest to a very small shooting zone. Though the actual distance between the two regions is far, the reflected regions adjoin with each other on the top surface of the prisms. Thus, the two regions can be captured synchronously with one image using a small field of view. Two types of configurations with 4 prisms and 6 prisms are compared using gas-liquid and liquid-liquid experimental results. The resolution of the two configurations is similar, while the maximum amplification ratio is smaller for the latter configuration with 6 prisms. The first type is more suitable for experimental studies focusing on the formation and breakup of dispersed phases near two branches. The second configuration is recommended for cases focusing on the formation and fully developed hydraulic characteristics of the dispersed phase. The proposed method is very efficient for studies of hydraulic, heat and mass transfer characteristics of multiphase flows in mini/micro channels.